Development of an instrument to assess the mental health of university students: validation of the Outcome Questionnaire-45 in a Hungarian sample - Matavovszky, Dominika; Nguyen Luu, Lan Anh; Karner, Orsolya (Frontiers in Psychology, 2024)
The Outcome Questionnaire is a self-report questionnaire developed mainly for treatment impact assessment and monitoring of status change because it can measure the cross-sectional condition very accurately by being sensitive to small changes. The present study aimed to psychometrically evaluate and validate the instrument on a sample of Hungarian university students. 7,695 higher education students (28.6% male, 68.8% female, 1% other, M = 23.7, SD = 6.78) participated in the study and completed a questionnaire package (OQ-45, Beck Depression Inventory, WHO Well-being Questionnaire-5, Connor-Davidson Resilience Scale, MOS-Social Support Survey, Maslach Burnout Inventory-SS) online, developed to measure general and more specific mental health conditions. The Hungarian version of the questionnaire has a high internal consistency (Cronbach’s alpha = 0.951). Based on the confirmatory factor analysis, the original three-factor version of the instrument (due to inadequate fit indicators) did not gain support in our sample. Five subscales were identified and subjected to content analysis in the exploratory factor analysis. Our final questionnaire consists of 39 items. The full scale and the subscales show a high correlation with other questionnaires measuring similar constructs. The psychometric indicators of the questionnaire are adequate and, therefore, considered reliable. The separation of the five factors was confirmed by construct and convergent validation. The questionnaire’s psychometric properties may be worth testing in the future on a clinical sample and a sample of adults from a wider age range. The use of the measurement tool has important implications in research areas beyond therapeutic impact assessment, as it may offer a bridging solution to the methodological problems encountered in the construction of complex questionnaire packages consisting of several instruments. International findings suggest that some items in the questionnaire are particularly sensitive to cultural context, so it is crucial to use a measure adapted to the region of the study sample. Other strengths of the questionnaire include its ability to address subclinical and clinical symptoms in one dimension and provide a comprehensive cross-sectional picture of the bio-psycho-social status of individuals, which allows systematic monitoring of a large and heterogeneous population (higher education students).